One step synthesis of ordered mesoporous carbons with two-dimensional mesostructure by soft templating method using mixed triblock copolymers. (February 2014) - Li, P.; Song, Y.; Tang, Z. H.; Yang, G. Z.; Guo, Q. G.; Liu, L.; Yang, J. H.
<x content-type="archive" xml:space="preserve">Abstract</x> Ordered mesoporous carbons (OMCs) with a two-dimensional mesostructure have been synthesised by organic–organic self-assembly of a mixture of poly(propylene oxide)-b-poly(ethylene oxide)-b-poly(propylene oxide) (PPO–PEO–PPO/PEO–PPO–PEO) amphiphilic triblock copolymers as templates, with soluble, low molecular weight phenolic resin precursor through the soft templating method. The hydrophilic/hydrophobic ratios were optimised to obtain OMCs. The microstructure of OMCs was analysed by small angle X-ray scattering, nitrogen adsorption isotherms and transmission electron microscopy. The results showed that the OMCs obtained have uniform pore size distribution centred at ∼3·5 nm with great surface area up to 731 m2 g−1 and large pore volume up to 0·44 cm3 g−1. Furthermore, the mesostructure of the OMCs obtained changes from a centred rectangular C2mm to a hexagonal p6mm by tuning the ratios of PEO/PPO.